Latrihal Media to Improve Fine Motor Ability in Student with Visual Impairment - Nurfadillah, Hesvia (JASSI ANAKKU, 2021)
The purpose of this study was to determine the use of latrihal media in improving fine motor skills in students with visual impairment. The methods used are lectures, demonstrations, and assignments. The subject of this research is 1 student with visual impairment at the special needs school, in Sumedang, West Java. The results showed that students experienced an increase in ability and had reached the Minimum Completeness Criteria of 65. In the initial ability, students get a score of 25 with a percentage of 25% and increase to a score of 72 with a percentage of 72%, so that there is an increase of 47%. Increased research is also indicated by the results of initial observations obtaining a score of 2 in the discipline aspect; a score of 1 on the conscientious aspect; score 1 on the aspect of concentration; and a score of 1 on the participatory aspect to a score of 3 on the discipline aspect; a score of 3 on the conscientious aspect; score 3 on the aspect of concentration; and a score of 3 on the aspect of participation in the final observation because students get direct experience using interesting media. This study demonstrates that the use of concrete learning media will make it easier to improve students' finger coordination skills. In addition, fine motor training media also makes it easier for teachers to guide students, especially for students with visual impairment.